2020
DOI: 10.1038/s41598-020-69478-x
|View full text |Cite
|
Sign up to set email alerts
|

Lead sulphide colloidal quantum dots for room temperature NO2 gas sensors

Abstract: colloidal quantum dots (cQDs) have been recently investigated as promising building blocks for low-cost and high-performance gas sensors due to their large effective surface-to-volume ratio and their suitability for versatile functionalization through surface chemistry. in this work we report on lead sulphide cQDs based sensors for room temperature no 2 detection. the sensor response has been measured for different pollutant gases including NO 2 , cH 4 , co and co 2 and for different concentrations in the 2.8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…GQDs offer significant advantages of low cost, high water solubility, stable fluorescence, tunable bandgap, low toxicity and good biocompatibility 8 11 , and thus making them a legitimate competitor to the traditional semiconductor quantum dots (QDs) (e.g. ZnS, TiO, CdSe, CdS, CdTe), which are expensive, cytotoxic, and show low-biocompatibility 12 . Owing to their unique properties, GQDs exhibit substantial potential for a wide range of promising applications in catalysis, sensors, bio-imaging, medical diagnosis, optoelectronics, and energy storage devices 10 , 11 , 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…GQDs offer significant advantages of low cost, high water solubility, stable fluorescence, tunable bandgap, low toxicity and good biocompatibility 8 11 , and thus making them a legitimate competitor to the traditional semiconductor quantum dots (QDs) (e.g. ZnS, TiO, CdSe, CdS, CdTe), which are expensive, cytotoxic, and show low-biocompatibility 12 . Owing to their unique properties, GQDs exhibit substantial potential for a wide range of promising applications in catalysis, sensors, bio-imaging, medical diagnosis, optoelectronics, and energy storage devices 10 , 11 , 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Efforts should be made to develop room-temperature sensors to reduce energy consumption with enhanced sensitivity. For example, UV irradiation [ 130 ], bimetallic decoration [ 131 ], use of quantum dots [ 132 ] or their combinations [ 133 ] are among different strategies that can reduce the sensing temperature even to room temperature. In addition, a fluctuation-enhanced sensing (FSA) approach can be used to improve the sensitivity of the sensors [ 134 , 135 , 136 , 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sensor prepared with a Pb to S ratio of 4:1 during synthesis showed a stronger response to NO 2 gas because of more Pb cations residing on the surface, where the adsorption of NO 2 molecules was improved, which was beneficial for sensing of NO 2 gas. In another study, the effect of the PbS QDs film thickness on the NO 2 gas response was reported [68]. The size of the QDs was ~4 nm and different QD films with thicknesses in the range from 500 nm to 1500 nm were deposited on the sensor substrate.…”
Section: Pbs Qd Gas Sensorsmentioning
confidence: 99%